Sistem Informasi Pengolahan Data Absensi dan Cuti Karyawan Berbasis WEB Studi Kasus Pada PT. Intinusa Selareksa - Muhammaddien Sunarto, Nur; Fatimah, Fety; Widhyaestoeti, Dahlia (Jurnal Etnik: Ekonomi-Teknik, 2023)
Maintaining and improving employee productivity is one of the efforts that can be done to enhance the company's success. To ensure that the quality of employee productivity is maintained, the company needs an information system that can manage employees and provide services to all employees. The problems faced by PT. Intinusa Selareksa includes the current attendance system that uses a barcode scanner. The attendance system has several weaknesses such as damage to the barcode scanner device, making it difficult to read the barcode code on employee identification cards, and many cases of lost or misplaced employee identification cards. Another problem faced is the non-computerized managerial activities such as the leave, permit, and overtime application process. This causes difficulties for the HRD department to provide information quickly and accurately because the report-making process is still manual. This research aims to obtain a system design result and develop a web-based attendance and leave data processing information system for employees. The system development method used in this research refers to the waterfall method. The stages of this research include analysis, design, implementation, and system testing. The system design uses Unified Modelling Language (UML). A website-based information system can present information related to employee administration management, specifically aimed at improving services in the HRD department